Hydrogen Auto‐transfer Synthesis of Quinoxalines from o‐Nitroanilines and Biomass‐based Diols Catalyzed by MOF‐derived N,P Co‐doped Cobalt Catalysts - Sun, Kangkang; Li, Dandan; Lu, Guo‐Ping; Cai, Chun (ChemCatChem, 2021)
A Co‐based heterogeneous catalyst supported on N,P co‐doped porous carbon (Co@NCP) is prepared via a facile in‐situ doping‐carbonization method. The Co@NCP composite features a large surface area, high pore volume, high‐density and strong basic sites. Furthermore, doping of P atoms can regulate the electronic density of Co. Therefore, Co@NCP exhibits good performance for the synthesis of quinoxalines from o‐nitroanilines and biomass‐derived diols under alkali‐free conditions. Heterogeneous catalysis: The synthesis of a Co‐based heterogeneous catalyst supported on N,P co‐doped porous carbon (Co@NCP) by a facile in‐situ doping‐carbonization method is reported. Co@NCP exhibits good performance for the synthesis of quinoxalines from o‐nitroanilines and biomass‐derived diols under alkali‐free conditions.